Hardware and Software Complex for Power Plant Management - V. A. Rybak; I. M. Rimarev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Today, the issues of transferring private households to independent energy sources, including solar panels and solar collectors, are relevant. The article examines software options for hardware systems that can be used to manage energy supply systems for private homes. Technologies for using independent energy sources in the energy consumption system are presented, as well as the mathematical model for their optimization for remote country houses.